Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Siswa Pada Materi Hukum Newton di SMA - Abas, Senti; Supartin, Supartin; Demulawa , Meilan (Universitas Pendidikan Mandalika, 2025)
Physics learning at the senior high school level often encounters problems related to low student motivation and weak conceptual understanding, especially in abstract topics such as Newton’s Laws. Teacher-centered instructional practices tend to limit students’ active involvement, resulting in unsatisfactory learning outcomes. Therefore, the application of student-centered learning models is required to improve students’ engagement and conceptual mastery. This study aimed to examine the effect of the Discovery Learning model on students’ learning outcomes in Newton’s Laws. The research employed a quantitative experimental approach using a One Group Pretest–Posttest Design involving one experimental class and two replication classes at SMA Negeri 1 Kabila during the 2024/2025 academic year. A total of 75 eleventh-grade students participated in the study. Students’ learning outcomes were measured using an essay test assessing cognitive levels of understanding (C2), application (C3), analysis (C4), and evaluation (C5). Data analysis included descriptive statistics, the Liliefors normality test, a one-tailed t-test, and N-Gain analysis. The results showed a significant improvement in students’ learning outcomes after the implementation of the Discovery Learning model. The mean posttest scores in all classes exceeded the Minimum Mastery Criterion of 75, with N-Gain values ranging from 0.72 to 0.78, which fall into the high category. The t-test results indicated that the calculated t-values were greater than the critical values, confirming a significant effect of the Discovery Learning model. These findings indicate that Discovery Learning is effective in enhancing students’ conceptual understanding and learning outcomes in physics. The study implies that Discovery Learning can be adopted as an effective instructional approach to promote active learning and improve the quality of physics education at the senior high school level.